Youths' Digital Literacy Skills: Critical Thinking to Participate in Elections - Handoko, Waluyo; Israwan Setyoko, Paulus; Kurniasih, Denok (Journal of Local Government Issues, 2023)
The purpose of this study is to examine how to enhance the critical thinking of young people through digital literacy skills. Furthermore, the ability to think critically is seen from the perspective of building active participation in general elections in Indonesia. A literature review was used as the research approach in this study.  The results show that based on the challenges of digital life, the younger generation falls into two categories: objects and subjects in general elections. The dominant key to the success of digital literacy lies in the ownership of digital literacy skills, more specifically leading to critical thinking in responding to all events in the general election phenomenon in Indonesia. The design of the digital literacy-based democracy movement includes viral party centers, online forums, digital party organizations, online campaigns, and online protests. Critical thinking in generating active participation in elections includes several elements: digital skills, ethics, safety, and culture. So that the output of active participation is in the form of supporting general elections, monitoring, channellings vote correctly, and being responsible.